The association of serum adipokines and vitamin D level in newly diagnosed women with breast cancer: a case-control study - Zahali, Zunura’in; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Jan Mohamed, Hamid Jan (2020)
This study was aimed to investigate the association of serum adipokines and vitamin D level with the risk of breast cancer. A case-control study was conducted on 78 women with newly diagnosed breast cancer and 86 healthy women, aged 21 to 59 years. Level of serum HMW adiponectin, visfatin, vitamin D and anthropometric parameters were determined. Mean serum adiponectin [2.9(1.6) vs 3.6(2.0)] and Vitamin D [14.5(7.5) vs 17.7(5.7)] concentrations were found significantly lower in cases group as compared to controls.group. The median serum visfatin of cases group was significantly higher than controls group [2.4(3.6) vs 1.7(2.1)]. Serum HMW adiponectin and vitamin D concentrations were found to be significantly associated with reduced risk of breast cancer (OR=0.79; 95% CI: 0.60-0.99, OR=0.90; 95% CI: 0.84-0.96). The risk of developing breast was 4.56-times (95% CI: 1.54-13.51) higher in women who had serum vitamin D <20 ng/ml as compared to those who had ≥20 ng/ml of serum vitamin D. Serum visfatin was seen to increase the risk of developing breast cancer in unadjusted model with OR=1.19 (95% CI: 1.01-1.39) although the association was insignificant after adjustments. We found that lower concentration level of HMW adiponectin and vitamin D may contribute to the development of breast cancer.